How house’s condition and facilities can reduce mental health problem, learn from COVID-19 pandemic: A systematic review - Wibowo, Andi Prasetiyo; Mardiah, Ainul (Edelweiss Applied Science and Technology, 2025)
This study examines the mental health implications of the COVID-19 pandemic and the impact of lockdown measures on domestic amenities, daily routines, and overall well-being. It further explores how the home environment can mitigate these adverse effects. A systematic review was conducted using the SCOPUS database, analyzing relevant publications up to February 2022. The findings were synthesized using a narrative review methodology to assess the relationship between lockdown measures, mental health, and the role of the home environment. The analysis indicates that lockdown measures significantly influence mental health, exacerbating stress, anxiety, and disruptions to daily life. However, a well-designed home environment can serve as a protective factor, mitigating these negative effects. Access to green spaces, areas for physical activity, and adaptable living spaces contribute positively to mental well-being. Furthermore, the role of technology in maintaining communication and providing entertainment proved essential in reducing feelings of isolation. The findings highlight the critical role of residential environments in supporting mental health during prolonged lockdowns. Homes that accommodate essential activities and provide access to restorative spaces can alleviate the psychological burden of restrictive measures. These insights underscore the importance of designing living spaces that enhance psychological resilience. Urban planners, architects, and policymakers should prioritize residential designs that incorporate green areas, flexible spaces, and digital connectivity to support mental well-being during future crises.